Análisis de la cultura empresarial desde el enfoque de la psicología organizacional, en las PYMES comerciales del Distrito Metropolitano de Quito, período 2008 – 2012 - Rodríguez Viteri, Martha Cecilia (2014)
The corporate culture is defined as the assets of the organizations where shared beliefs, customs, traditions and values among its employees there, and, being human talent the main element of culture, this research enriches their study emphasizing the organizational psychology of Small and Medium-sized trading company in the Metropolitan District of Quito. In the context of the study is reflected in the theoretical framework containing coarse concepts of corporate culture, their classification, elements, features and functions that distinguish one organization from another. It also conceptualizes organizational psychology and its objectives, as well as behavior and organizational climate variables influencing the culture. For the field research was considered the focal group of commercial SMEs, members of the Chamber of Small and Medium Enterprise CAPEIPI union representing these productive sectors. The survey information was made through a survey whose contents included variables such as leadership, communication, management of human talent, environment and jobs, efficiency and productivity, innovation and change, motivation, interpersonal relationships, pride and belonging; parameters which were analyzed by independent variables such as age, occupation, gender and seniority. As a further contribution to the research, a model of cultural development for SMEs, which is presented as a multidisciplinary tool for leaders, guided under theoretical and scientific, with a scheme based on the psychosocial development of the individual and a rich text discussed with the addition of administrative and organizational criteria from the perspective of managerial skills, in order to generate more competitive, profitable and productive SMEs.